The relationship between taxes and economic growth: evidence from Serbia and Croatia - Kalaš, Branimir; Mirović, Vera; Milenković, Nada (The European Journal of Applied Economics, 2018)
This study presents an empirical analysis of taxes and economic growth in Serbia and Croatia in the period 2007-2016. In order to identify the impact of tax forms on economic growth and their relationship, the authors decided to set up a panel regression where gross domestic product is the dependent variable, while corporate income tax, value added tax, social security contributions and excises are independent variables. The results of random effect model have shown that corporate income tax, value added tax and social security contributions have a positive impact on the gross domestic product, while excises affect the gross domestic product negatively. However, only value added tax has a statistically significant impact on economic growth in these countries, with each increase in revenue from this tax contributing to the growth of gross domestic product in the observed period.